1996
DOI: 10.1177/070674379604101002
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Treatment of Depression: A Metaanalysis

Abstract: We conclude that the superior efficacy of antidepressants over placebo can be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
0
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 38 publications
8
59
0
3
Order By: Relevance
“…In Joffe and others' metaanalysis of the effectiveness of antidepressants, it is possible to compute an effect size of r = 0.24 (22). To capture an effect of that size reliably, a sample size of 120 (60 per group) is required to find significant results 80% of the time (K Parker, personal communication, March 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In Joffe and others' metaanalysis of the effectiveness of antidepressants, it is possible to compute an effect size of r = 0.24 (22). To capture an effect of that size reliably, a sample size of 120 (60 per group) is required to find significant results 80% of the time (K Parker, personal communication, March 2004).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Up to 40% of depressed patients fail to show a response to fi rst-line antidepressant drug treatment, 5 and of those that do respond, only a proportion will achieve full recovery.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Up to 40% of depressed patients fail to show a response to fi rst-line antidepressant drug treatment, 5 and of those that do respond, only a proportion will achieve full recovery. 6 One cohort study of primary care patients found that 60% of depressed patients treated with medication and 50% with milder depression still met the criteria for caseness at 1 year.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(20) exposant une méta-analyse y réplique en concluant : « Une ana lyse plus at ten tive soutient la validité d'études rapportant des essais avec les antidépresseurs qui avaient été présentées comme de validité douteuse. » Cette réplique rejoint le constat en faveur de l'efficacité des antidépresseurs présenté dans une autre méta-ana lyse portant sur les essais réalisés en tre 1966 et 1995 (21). Des progrès sont cependant vivement attendus quant à la manière de publier les résultats dans toute la doc u men ta tion médicale, comme en témoigne une re vue cri tique et lucide sur la ques tion (22).…”
Section: Les Antidépresseurs Sont-ils Efficaces Pour Traiter La Dépreunclassified